Plants regulate grassland arthropod communities through biomass, quality, and habitat heterogeneity - Rebecca M. Prather; Michael Kaspari (Ecosphere, 2019)
Abstract Habitat heterogeneity affects both biotic and abiotic factors important in determining arthropod community composition. In a sandy, mixed‐grass prairie in the southern Great Plains, we used clipping and NPK fertilization to manipulate plant biomass, habitat heterogeneity, and plant quality to quantify their relative effects on the abundance and diversity of its arthropod community. Both clipping and fertilization treatments affected plant biomass and microclimate, including light availability, temperature, and humidity. By decreasing plant biomass, clipping simplified habitat structure and resulted in reduced arthropod abundance and diversity and increased arthropod activity. This reduction appeared to be mediated by fertilizer addition, which increased total plot carbon, plant biomass, and habitat volume, resulting in lower average surface temperature and higher average humidity. By itself, increasing plant biomass through fertilization increased arthropod abundance, activity, and richness. In addition, we show that changing microclimate and plant biomass promoted shifts in arthropod community composition. These results demonstrate the role of habitat heterogeneity and plant quality in structuring arthropod community composition, specifically by regulating microclimate and providing habitat space.